Investigating the effect of machining parameters on EDMed components a RSM approach / Manoj Kumar Pradhan and Chandan Kumar Biswas - Pradhan, Manoj Kumar; Biswas, Chandan Kumar (UiTM Press, 2010)
The effects of the machining parameters in electrical-discharge machining on the machining characteristics of AISI D2 steel workpiece has been investigated in this research. The response functions considered are Material Removal Rate (MRR) and surface roughness (Ra), while machining variables are pulse current, pulse on time, pause time and gap voltage. A Response surface methodology was used to reduce the total number of experiments. Empirical models correlating process variables and their interactions with the said response functions have been established. The significant parameters that critically influenced the machining characteristics were examined and developed predictive models. Analyzing these models, it is found that pulse current is the most significant parameter for both the responses, followed by pulse off time, gap voltage and pulse on time for MRR, and pulse on time and gap voltage for Ra. The model sufficiency is very satisfactory as the coefficient of determination (R2) is found to be greater than 98.3% and R2 adj is over 97.6%. These models can be used for selecting the values of process variables to get the desired values of the response parameters.